The Development of the Secondary Trauma in Student Affairs Professionals Scale (STSAP). Issue 1 (1st January 2019) - Lynch, R. Jason; Glass, Chris R.
Abstract : College student affairs professionals increasingly act as first responders to student crises. This article describes the development and validation of an instrument designed to measure symptoms of secondary trauma within a sample of student affairs professionals ( n  = 617). Using exploratory and confirmatory factor analysis, the instrument and its subscales were found to demonstrate evidence of validity and reliability. Authors discuss implications for research and practice regarding secondary trauma in student affairs.